EFEKTIVITAS KINERJA DEWAN PENGAWAS SYARIAH TERHADAP KEPATUHAN SYARIAH DI BMT (STUDI KASUS PADA BMT AMYRA PONPES AL-AMANAH AL-GONTORY) - Umiyati; Haqila Azzikri, Muhammad; Aziz, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effectiveness of the Sharia Supervisory Board (SSB/DPS) performance in ensuring sharia compliance at Baitul Maal wa Tamwil (BMT) AMYRA Ponpes Al-Amanah Al-Gontory. Employing a qualitative descriptive approach, primary data were gathered through semi-structured interviews with DPS members, management staff, and BMT members, while secondary data were derived from academic journals and institutional documents. The analytical framework integrates six DPS supervisory assessment indicators adapted from prior literature: integrity, competence, financial reputation, duties and obligations, product supervision based on sharia principles, and concurrent positions. The findings demonstrate that DPS at BMT Syahida performs a strategic supervisory function through periodic audits, akad verification, and product review mechanisms aligned with DSN-MUI fatwas. Nevertheless, challenges persist, particularly concerning limited human resource capacity within DPS and low sharia literacy among management and members. This study addresses a gap in the existing literature by focusing on a university-based Islamic microfinance institution, offering academic contributions to sharia governance research and practical recommendations for improving DPS performance.